HUBUNGAN ANTARA BIMBINGAN KARIR DAN PRESTASI BELAJAR KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA PADA SISWA KELAS XI PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN DI SMK AL MUNAWWARAH KESUGIHAN CILACAP TAHUN PELAJARAN 2014/2015 - Djati Winarko; Setuju Setuju (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to know (1) correlation between carrier guidance with interest in entrepreneurship; (2) correlation between learning achievement with interest in entrepreneurship; and (3) correlation between carrier guidance and learning achievement with interest in entrepreneurship among the eleventh grade students of TKR at SMK Al Munawwarah Kesugihan Cilacap in the academic year 2014/2015. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression with two predictors. This study shows that (1) there was a positive and significant correlation between carrier guidance with interest in entrepreneurship with the score of significance under 5%; (2) there was a positive and significant between learning achievement with interest in entrepreneurship with the score of significance under 5%; and (3) there was a positive and significant between carrier guidance and learning achievement with interest in entrepreneurship with the score of significance under 5% among the eleventh grade students of TKR at SMK Al Munawwarah Kesugihan Cilacap in the academic year 2014/2015. The score of determinant coefficient (R2) was 59.9%. It means that carrier guidance and learning achievement gave positive contribution 59.9% toward the students’ interest in entrepreneurship, while 40.1% was influenced by other factors that were not discussed in this study. The carrier guidance gave contribution 13.2% toward interest in entrepreneurship and learning achievement gave contribution 26.7% toward with interest in entrepreneurship with the total contribution 59.9%.